Simultaneous voltammetric detection of clenbuterol and ractopamine using violet phosphorene–MWCNT nanocomposite sensor optimized by multi-objective particle swarm algorithm - Chen, Tao; Chen, Yiji; Xiong, Yao; Guo, Zhoujun; Wu, Ruimei; Ai, Shirong; Wen, Yangping (Mikrochimica acta (1966), 2025)
The illegal use of β-agonists like clenbuterol (CLB) and ractopamine (RAC) as livestock growth promoters poses severe threats to human health. To address this, we developed a novel electrochemical sensor based on violet phosphorene (VP) and carboxylated multi-walled carbon nanotubes (COOH-MWCNTs) with Nafion-isopropanol mixed solution for simultaneous voltammetric detection of CLB and RAC in beef. The sensing platform was optimized through response surface methodology coupled with particle swarm optimization, enabling multi-objective parameter (VP concentration, COOH-MWCNTs concentration, and pH value) refinement that enhanced sensitivity while minimizing experimental trials. This design leveraged the synergistic properties of VP (high carrier mobility) and COOH-MWCNTs (electrocatalytic activity), yielding a sensor with ultra-low detection limits of 5.8 nM for CLB and 6.4 nM for RAC, excellent selectivity with negligible interference from biological matrices, and high stability. Support vector machine (SVM) nonlinear models achieved robust quantification ( R 2 > 0.9948 and RPD > 7.09 for both analytes), validated by high recoveries (98.4–103.1% for CLB and 96.4–103.7% for RAC) in beef samples. This work establishes a rapid, cost-effective platform for monitoring β-agonist residues, advancing food safety surveillance. Graphical Abstract